Multimodal Microstructure and Mechanical Properties of AZ91 Mg Alloy Prepared by Equal Channel Angular Pressing plus Aging - Zhenquan Yang; Aibin Ma; Huan Liu; Jiapeng Sun; Dan Song; Ce Wang; Yuchun Yuan; Jinghua Jiang (Metals, 2018)
Developing cost-effective magnesium alloys with high strength and good ductility is a long-standing challenge for lightweight metals. Here we present a multimodal grain structured AZ91 Mg alloy with both high strength and good ductility, prepared through a combined processing route of low-pass ECAP with short-time aging. This multimodal grain structure consisted of coarse grains and fine grains modified by heterogeneous precipitates, which resulted from incomplete dynamic recrystallization. This novel microstructure manifested in both superior high strength (tensile strength of 360 MPa) and good ductility (elongation of 21.2%). The high strength was mainly attributed to the synergistic effect of grain refinement, back-stress strengthening, and precipitation strengthening. The favorable ductility, meanwhile, was ascribed to the grain refinement and multimodal grain structure. We believe that our microstructure control strategy could be applicable to magnesium alloys which exhibit obvious precipitation strengthening potential.